2006
DOI: 10.1111/j.1365-313x.2006.02656.x
|View full text |Cite
|
Sign up to set email alerts
|

Auxin controls local cytokinin biosynthesis in the nodal stem in apical dominance

Abstract: SummaryIn intact plants, the shoot apex grows predominantly and inhibits outgrowth of axillary buds. After decapitation of the shoot apex, outgrowth of axillary buds begins. This phenomenon is called an apical dominance. Although the involvement of auxin, which represses outgrowth of axillary buds, and cytokinin (CK), which promotes outgrowth of axillary buds, has been proposed, little is known about the underlying molecular mechanisms. In the present study, we demonstrated that auxin negatively regulates loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

31
346
4
10

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 429 publications
(391 citation statements)
references
References 56 publications
(104 reference statements)
31
346
4
10
Order By: Relevance
“…While likely a trigger for bud release, cytokinin may also promote auxin production and basipetal auxin transport out of growing buds, which consequently represses the production of cytokinin lower in the stem and limits its availability for other buds (Bangerth et al, 2000;Tanaka et al, 2006;Shimizu-Sato et al, 2009).…”
mentioning
confidence: 99%
“…While likely a trigger for bud release, cytokinin may also promote auxin production and basipetal auxin transport out of growing buds, which consequently represses the production of cytokinin lower in the stem and limits its availability for other buds (Bangerth et al, 2000;Tanaka et al, 2006;Shimizu-Sato et al, 2009).…”
mentioning
confidence: 99%
“…Although an antagonistic role of auxin and cytokinin in the regulation of apical dominance has been postulated for decades, little is known about the underlying molecular mechanisms. Recent studies have shown that auxin can regulate the expressions of IPT genes and that cytokinin biosynthesis is directly affected by auxin in local shoots [32,33], suggesting that auxin may modulate cytokinin concentration and thus represses AM outgrowth [31,[34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Although an antagonistic role of auxin and cytokinin in the regulation of apical dominance has been postulated for decades, little is known about the underlying molecular mechanisms. Recent studies have shown that auxin can regulate the expressions of IPT genes and that cytokinin biosynthesis is directly affected by auxin in local shoots [32,33], suggesting that auxin may modulate cytokinin concentration and thus represses AM outgrowth [31,[34][35][36].Recent studies on a series of branching mutants, such as more axillary growth (max) of Arabidopsis [37][38][39][40], ramosus (rms) mutants of pea [41][42][43], decreased apical dominance (dad) mutants of petunia [44,45] and dwarf (d) mutants of rice [46][47][48][49][50][51], have revealed strigolactone as a second messenger of auxin action on the control of AM outgrowth [52,53]. Strigolactones, a group of terpenoid lactones that have been found in root exudates of diverse plant species, are synthesized from carotenoids in roots and transported acropetally or synthesized locally to repress the outgrowth of shoot branches [38,[54][55][56].…”
mentioning
confidence: 99%
“…Auxin, derived from the shoot apex and moving basipetally, inhibits growth of axillary buds, while cytokinin, thought to be derived from the roots, promotes their growth (Cline, 1994;Leyser, 2003). Tanaka et al (2006) indicated that one role of auxin is to repress local biosynthesis of cytokinins in the nodal stem and that, after decapitation, cytokinins are locally biosynthesized in the nodal stem rather than in the roots. The reduced main shoot elongation during winter (December) probably restricted apical dominance and thus more axillary buds were developed at this period (Table 3), resembling the species behaviour in the wild, where new vegetation sprouts in winter.…”
Section: Establishment Of Rooted Cuttingsmentioning
confidence: 99%